(untitled) (Південний архів (історичні науки), 2022)
The purpose of the study is to consider the peculiarities of the growth of the number of Ukrainian media during the intensification of the liberation struggle, revolutionary changes. To study the interdependence of key, turning points in the history of Ukraine with the development of an independent national press. The purpose of the study is to consider the peculiarities of the growth of the number of Ukrainian mass media in the period of intensification of the liberation struggle and revolutionary changes. Understand the interdependence of key, turning points in the history of Ukraine with the position of the independent national press. To create a more thorough vision of the problem, comparative parallels were drawn with similar processes in the history of other nations. The methodological basis of the study were concrete-historical, comparative and historical-analytical methods. The principles of objectivity, historicism, multifactoriality are used. The media is a powerful institution of society, which is an influential factor in building the trajectory of development of the national community. The government of any country tries to project public opinion by selecting information in the media or establishing full control over it. Therefore, the media are involved in the confrontation that takes place in the plane of power-opposition, power-society, enslaver-captive, interventionist-defender. Historical retrospective shows that the media were freed from the control of power (totalitarian regime) during political riots, revolutions, wars. On the eve of these events, and especially in the course of their course, the media inform and activate society, stimulate the search for truth and form a willingness to pay a high price for the truth. In the history of the Ukrainian struggle for freedom, the media have played an important role in the consolidation and integration of the community, the revival of the idea of political independence and ethnic identity. As in other enslaved peoples, revolutions or increasing liberation resistance were accompanied by an increase in the number of printed publications. After the defeat of the liberation resistance, the occupation regimes directed brutal repression at the destruction of Ukrainian obscene periodicals. Thanks to the existence of numerous independent press during the Ukrainian Revolution of 1988–1999, it was possible to win the information war with the Soviet totalitarian regime. It is important to continue the study of the issue raised in this article, as the importance and influence of the press on the liberation struggle of the Ukrainian people is a main topic of study.